2022
DOI: 10.1149/ma2022-0112869mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature WS2 Metal-Organic Chemical Vapor Deposition Using n-Bunc-W(CO)5 for W Precursor

Abstract: Tungsten disulfide (WS2) is one of the representative two-dimensional layered materials, and its applications in various fields have been actively studied due to its preferable properties such as reasonably wide band gap (monolayer: 2.03 eV, bulk: 1.32 eV) [1] and excellent stability. In particular, large area, a few layer WS2 has a high potential as channel material for MOSFET in the next generation LSI. In most of the WS2 CVD reported so far, WF6 or W(CO)6 has been widely used for tungsten precursor as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…This may be due to the different strains that the grown WS 2 thin film undergoes. [38][39][40] These results are consistent with our previous study 41) and those presented in other studies, [42][43][44] which verify that the films near the substrate surface have a 2H structure. This is consistent with the XPS results.…”
Section: Resultssupporting
confidence: 92%
“…This may be due to the different strains that the grown WS 2 thin film undergoes. [38][39][40] These results are consistent with our previous study 41) and those presented in other studies, [42][43][44] which verify that the films near the substrate surface have a 2H structure. This is consistent with the XPS results.…”
Section: Resultssupporting
confidence: 92%
“…Likewise, the partition of C 1s spectra is linked to C–Ti, C–C, CO, and O–CO, which can be found at 283.9, 286.7, 288.2, and 292.6 eV, respectively. All of the deconvolution of the individual signal also well matched with the previous findings. …”
Section: Resultssupporting
confidence: 86%
“…These values are consistent with the previous literature. Following relaxations, self-consistent field (SCF) calculations were conducted, and the density of states for α-SnS, β-SnS, and π-SnS structures are plotted in Figure S2e,f. The analysis revealed that β-SnS exhibited the lowest band gap of 0.52 eV among all considered SnS phases, aligning with previous theoretical studies . The minimal band gap or maximum conductivity in β-SnS may contribute to the superior electrochemical performance.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations